PLANNING AND PROGRAMING OF THE TRAINING PROCESS WITH YOUNG SPRINTERS IN THE PREPARATORY PERIOD - Rade Stefanović; Branimir Mekić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
the training process, it is necessary to know the rules and to apply the leading factors in time (the application of the means of physical exercises, methods, organizational forms of work and the scope optimization of the load intensity) which contribute to the effi ciency of the training process. The morphologic status represented by the information on longitudinal and transferal dimensionality of the skeleton as well as the information on the body volume has the doubtless but relatively small signifi cance for achieving the results in sprinter running as with men as well as with women. Sport result in the training process is the product of made selection, regular organization of the working methods and all this in compliance with the individual characteristics of a sportsman. The plan and the basic division of the activities are based on the exercises for loosening up, speeding up and on load exercises in all forms of the training process